Size-dependent axonal bouton dynamics following visual deprivation in vivo - Sammons,RP; Clopath,C; Barnes,SJ (Cell Reports, 2018)
Persistent synapses are thought to underpin the storage of sensory experience. Yet, little is known about their structural plasticity in vivo. We investigated how persistent presynaptic structures respond to the loss of primary sensory input. Using in vivo two-photon (2-P) imaging we measured fluctuations in the size of excitatory axonal boutons in L2/3 of adult mouse visual cortex after monocular enucleation. The average size of boutons did not change after deprivation, but the range of bouton sizes was reduced. Large boutons decreased and small boutons increased. Reduced bouton variance was accompanied by a reduced range of correlated calcium mediated neural activity in L2/3 of awake animals. Network simulations predicted that size-dependent plasticity may promote conditions of greater bidirectional plasticity. These predictions were supported by electrophysiological measures of short and long-term plasticity. We propose size-dependent dynamics facilitate cortical reorganization by maximising the potential for bidirectional plasticity.